Phytochemical Composition of Aqueous Crude Extracts of Selected Pesticidal Plants used against Brassica Vegetable Pests - Lamara, Racheal; Andama, Morgan; Olet, Eunice A. (International Journal of Current Microbiology and Applied Sciences, 2020)
The phytochemistry of five plants (Phytolacca dodecandra, Azadirachta indica, Capsicum frutescens, Allium cepa and Tagetes minuta) was determined to evaluate their potential as sources of alternative pesticides against Brassica vegetable pests. Crude aqueous plant extracts were prepared, on which quantitative and qualitative analysis were performed using standard methods. Tannins and alkaloids were found in all plants examined with their highest quantities obtained in T. minuta at 0.4494 mgml-1and 0.1560 mgml-1 respectively. Steroids were highest in C. frutescens and A. indica at 2.2791 mgml-1 each. Saponins were more inP. dodecandra(31.06%) and flavonoids were highest in C. frutescens(26.13%). It was evident that C. frutescens, A. indica and T. minuta had higher quantities of phytochemicals. This may be responsible for them being more effective pesticides against Brassica vegetable pests than Allium cepa and P. dodecandra which had lower quantities or absence of some phytochemicals.
Keywords: Aqueous Extracts; Pesticidal Plants; Phytochemicals; Quantitative Analysis